The Effect of Light Intensity on Electrical Energy Produced by Polycrystalline Solar Panels - Falaqi; Tri Nur Arifin (International Journal Science and Technology, 2025)
This study analyzes the effect of sunlight intensity on the electrical energy generated by polycrystalline solar panels. The solar power plant system was designed simply and measurements were taken over three days using a lux meter, thermometer, ampere meter, and power meter. Data were analyzed using SPSS through correlation tests and multiple linear regression. The results show that light intensity (lux) has a dominant influence with an average contribution of 68.2% to electrical power. The maximum power recorded was 76 Watts on May 18, 83.3 Watts on June 1, and 85 Watts on June 27, 2025. Other environmental variables such as panel surface temperature, ambient temperature, and humidity also have an influence but on a smaller scale. In conclusion, light intensity plays a significant role in solar panel performance and is a major factor in solar power plant system planning.